CHALLENGES OF INTEGRATING RELIGION AND SPIRITUALITY INTO PSYCHOTHERAPY integrity, competence, and cultural pluralism in clinical pra. - Martin, Francis A. ([S.l.] : ROUTLEDGE, 2024)
This book examines personal and professional understandings of religion in psychotherapy and advocates for integrity, competency, and cultural pluralism in clinical practice. Amajor feature of this book is that it confirms the massive proliferation of religion-oriented approaches tocounseling and therapy in recent years. It attributes this rise to opportunism and exaggerated individualism among therapists and to the frequent failures of professional associations, clinical preparation programs, and other influences. In response to these influences, it identifies the need for guiding principles for integrating religion into therapy, discusses the religious issues that clients bring to therapy, and advocates for major changes in clinical practice, with emphasis on integrity and competence. Building on a large volume of research and using evidence-based conclusions, it clarifies how these two major features of contemporary life can be integrated with integrity and competence. The author maintains that religion should be a feature of the practice of counseling and therapy, so long as it addresses the clinically relevant needs of clients. However, it also explores how the religion of counselors and therapists often expresses the needs of counselors and therapists, instead of addressing the needs of their clients. In the context of these questions and discussion of contentious challenges, this book provides guidelines for relating religion with clinical practice and recommends needed actions by clinical preparation programs, professional associations, individual therapists, state legislatures, licensing boards, social service agencies, and corporations. All of this stands on the conspicuous need for professional accountability in the delivery of mental health care.
Keywords: Psychoanalysis and religion; PSYCHOLOGY / Psychotherapy / Counseling; RELIGION / Spirituality